2017
DOI: 10.1101/101360
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wilm’s tumor 1 promotes memory flexibility

Abstract: Remembering and forgetting are important aspects of normal behavioral adaptation; however, the molecular basis of forgetting has been less studied. Using rat and mouse models we find that WT1, a transcriptional repressor that is activated in the hippocampus by LTP producing stimuli and behavioral memory, enables forgetting. Acute or tonic knockdown of WT1 did not affect short-term memory but enhanced long-term memory and enables a switch from circuit to cellular computation in the hippocampus. A control theory… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 96 publications
0
7
0
Order By: Relevance
“…Although only eight genes were differentially expressed based on their corrected P ‐value (FDR < 0.05, Appendix Fig S7D), analysis of transcription factor binding signatures ( P < 0.01, FC < −2, 115 genes in total) revealed that 29.6% of downregulated genes contained CREB1 response elements in their promoter region (Fig 5F). On the other hand, 66 out of 238 significantly upregulated genes ( P < 0.01, FC > 2) were regulated by the transcription activity WT1 (Fig 5G), which has recently been described as a crucial regulator of synaptic function and neuronal excitability (Mariottini et al , 2019). Intriguingly, among downregulated genes with CREB1 response elements, we identified genes encoding for proteins with a function in protein and vesicle trafficking ( Clasp1 , Gdi2 , Sgms1 , Vps13b ; Fig 5H), suggesting that autophagy might indirectly regulate intracellular membrane trafficking by controlling the PKA/CREB1 signaling.…”
Section: Resultsmentioning
confidence: 90%
“…Although only eight genes were differentially expressed based on their corrected P ‐value (FDR < 0.05, Appendix Fig S7D), analysis of transcription factor binding signatures ( P < 0.01, FC < −2, 115 genes in total) revealed that 29.6% of downregulated genes contained CREB1 response elements in their promoter region (Fig 5F). On the other hand, 66 out of 238 significantly upregulated genes ( P < 0.01, FC > 2) were regulated by the transcription activity WT1 (Fig 5G), which has recently been described as a crucial regulator of synaptic function and neuronal excitability (Mariottini et al , 2019). Intriguingly, among downregulated genes with CREB1 response elements, we identified genes encoding for proteins with a function in protein and vesicle trafficking ( Clasp1 , Gdi2 , Sgms1 , Vps13b ; Fig 5H), suggesting that autophagy might indirectly regulate intracellular membrane trafficking by controlling the PKA/CREB1 signaling.…”
Section: Resultsmentioning
confidence: 90%
“…On the other side, 66 out of 238 significantly upregulated genes (p<0.01, FC>2) were regulated by the WT1 transcription activity (Fig. 4I), which has been recently described as a crucial regulator of synaptic function and neuronal excitability ( 33 ). Intriguingly, among downregulated genes with CREB1 response elements, we identified genes encoding for proteins with a function in protein and vesicle trafficking ( Clasp1, Gdi2, Sgms1, Vps13b ) (Fig.…”
Section: Resultsmentioning
confidence: 84%
“…All processed samples had a RIN value ≥ 9. The seq library was prepared with a standard TruSeq RNA Sample Prep Kit v2 protocol (Illumina), as described previously (Mariottini et al, 2019). Size and concentration of the RNA-seq libraries was measured by the Agilent 2100 Bioanalyzer using the DNA 1000 assay (Agilent) before loading onto the sequencer.…”
Section: Spinal Cordmentioning
confidence: 99%
“…RNA libraries were sequenced on the Illumina HiSeq 2000 System with 100 nucleotide single-end reads, according to the standard manufacturer's protocol (Illumina). For RNA-seq data analysis, Star 2.5.4b and bowtie2 2.1.0, samtools 0.1.7 and cufflinks 1.3.0 were used as described previously (Stillitano et al, 2017;Hansen et al, 2019;Mariottini et al, 2019). Before read alignment, we identified the sample with the lowest read counts and downsampled all other samples to the same number of read counts by randomly removing excessive reads to prevent distortion of RNA-seq results by read count imbalances, as described previously (Stillitano et al, 2017).…”
Section: Spinal Cordmentioning
confidence: 99%